Complete Genome Sequence of Bacilli bacterium Strain VT-13-104 Isolated from the Intestine of a Patient with Duodenal Cancer - Tetz, George (Genome Announc, 2015)
We report the complete genome sequence of Bacilli bacterium strain VT-13-104 isolated from the intestine of a patient with duodenal cancer. The genome is composed of 3,573,421 bp, with a G+C content of 35.7%. It possesses 3,254 predicted protein-coding genes encoding multidrug resistance transporters, resistance to antibiotics, and virulence factors.